Hard ticks (Acari: Ixodidae) associated with birds in Europe: Review of literature data - Keve, Gergő; Sándor, Attila D.; Hornok, Sándor (Frontiers in Veterinary Science, 2022)
Hard ticks (Acari: Ixodidae) are considered as the most important transmitters of pathogens under the temperate zone including most of Europe. In the era of climate change tick-borne diseases are predicted to undergo geographical range expansion towards the north, which regions are connected to southern parts of the continent by bird migration. This alone justifies the importance to synthesize knowledge on the association of tick species with avian hosts. In addition, birds represent the taxonomically and ecologically most diverse part of urban vertebrate fauna, frequently occurring in gardens and near animal keeping facilities, thus playing a significant role in the dispersal of ticks and tick-borne pathogens in synanthropic environments. In light of this, the primary aim of this review is to provide a comprehensive reference source (baseline data) for future studies, particularly in the context of discovering new tick-host associations after comparison with already published data. For this purpose, the records on the ixodid tick infestation of birds were assessed from nearly 200 papers that were published since 1952. In this period, 37 hard tick species were reported from 16 orders of avian hosts in Europe. Here we reviewed the list of these tick species, followed by the English and Latin name of all reportedly infested bird species, also including the tick developmental stage and country of origin whenever this information was available. These data allowed a first-hand analysis of trends how and which developmental stage of ticks tend to infest avian hosts in general. Five tick species that were frequently reported from birds and show a broad geographical distribution in the Western Palearctic (Ixodes arboricola, I. frontalis, I. ricinus, Haemaphysalis concinna and Hyalomma marginatum) were also selected for statistical comparisons. Differences were demonstrated between these tick species in their association with bird species that either typically feed from the ground or on the contrary, rarely occur at the soil level. The ecology of these five bird-infesting tick species is also illustrated here according to avian orders, taking into account the ecology (habitat type) and activity (circadian rhythm and feeding level) of most bird species that represent a certain order.